PENGEMBANGAN SOFT-ACTUATOR DENGAN PENDEKATAN ADDITIVE MANUFACTURING YANG MENDUKUNG GERAKAN FLEKSI DAN EKSTENSI SECARA AKTIF - John Binsar Ganda Silaban, Paul
The hand rehabilitation process for post-stroke patients takes a very long time and is not effective. Currently are available robotic tools, namely rigid robotics and soft robotics. Rigid robotics can speed up the rehabilitation process, but this tool has a stiff material that easily causes joint fatigue and have a low level of safety. Therefore, a soft physiotherapy tool was developed, namely soft robotics. The driving component of a soft robot is known as a soft actuator. From their shape, soft actuator has various types, ranging from McKibben air muscles, fiber-reinforced actuators, and pneumatic network actuators (PneuNet). The PneuNet type has better-bending force capability than other actuator types. Therefore, this research will focus on the design and fabrication of the PneuNet-type soft actuator and test the characteristics of the soft actuator. This study carried out fabrication using the principles of the Additive Manufacturing (AM) 3D printing approach. The AM approach consists of four stages, among others: 3D model with CAD, carrying out the meshing process, carrying out the slicing process with Simplify 3D, and the fabrication process with a Fused Deposition Modeling (FDM) 3D printer model. In the fabrication process, aspects that need to consider are the soft actuator 3D design form, slicing parameters with Simplify 3D software, the type of filament used, and the fabrication process using the 3D printing method. After the fabrication is successful, the soft actuator does a characteristic test. This test will focus on two stages: the relationship between input pressure and the actuator bending angle and testing the system response when given an input step. Retrieval of actuator bend angle data using a series of electro-pneumatic systems. The MPX 5700AP pressure sensor will read the air pressure value on the soft actuator. Air flowing into the soft actuator will cause the soft actuator to flex or extend. Measurement of the bending angle of the soft actuator using a flex sensor. The test results show that the soft actuator can do a bend angle of 70°-90° with an input pressure of 100-120 kPa. For higher pressures, namely 300 kPa, the soft actuator can do a bend angle of 100°-168°. Based on the results of dynamic characteristic testing, the soft actuators show a step response of order 1.